(untitled) (Asian Journal of Plant Biology, 2023)
Endophytic fungi are microscopic organisms that live inside plant tissue. They can create a vast array of enzymes and metabolites that present a variety of biological activities without causing any visible indications of their existence. Due to their extensive use in many industries and their simplicity in production, stability, and optimization, fungal enzymes have attracted attention. This paper describes potential applications for the enzymes made by endophytic fungus and explores their use in diverse industries. Additionally, endophytic fungi may develop into fresh sources of industrially valuable enzymes like lipases, amylases, and proteases. Endophytes have rarely been used as sources of industrially relevant enzymes due to the diversity of plants that are readily available. In view of that, search for endophytes from plants with the potential of industrial enzymes is of paramount importance.